Effect of grape seed proanthocyanidin extract on intestine, slaughter performance, lipid metabolism and meat quality of broilers - HOU Fuyin; YANG Zhiqing; CHEN Changkuan; SHI Kai; JIN Chongfu; CHEN Yingjiang (浙江大学学报. 农业与生命科学版, 2019)
In order to explore a green feed additive to reduce the abuse of antibiotics in livestock and poultry farming, grape seed proanthocyanidin extract (GSPE) was selected to study its effects on animal immune protection, growth development and meat quality. In this study, by fermentation bed and cage-free net rearing mode 360 30-day-old broilers were randomized into four groups, with three replicates including 30 broilers each. Broilers in the control group were fed with basal diet, while broilers in the treatment groups were provided with the basal diet supplemented with 100, 200 and 400 mg/kg GSPE, respectively. The experimental period was both 40 d. The results showed as follows: 1) Compared with the control, supplementation with 400 mg/kg GSPE significantly increased the broiler ratio of duodenum villus length/crypt depth (P<0.05), and also induced an increase of goblet cell mucoprotein amount to a certain extent (P>0.05). The supplementation with 100 and 200 mg/kg GSPE promoted the development of broiler intestine without remarkable difference (P>0.05). 2) GSPE improved the slaughter performance of broilers, and the supplementation with 400 mg/kg GSPE possessed the best effect, which significantly increased the percentage of breast muscle than that of the control group (P<0.05). 3) Total serum cholesterol reduced significantly in the treatment when supplemented with 400 mg/kg GSPE (P<0.05) in comparison of the control group. Meanwhile, the supplementation with 100 and 200 mg/kg GSPE decreased triglycerides and low density lipoprotein cholesterol at different levels (P>0.05), but increased the high density lipoprotein cholesterol (P>0.05). 4) The shear force of broiler breast muscle and crude fat of leg muscle were significantly decreased when compared with the control group (P<0.05). Moreover, 200 mg/kg GSPE also largely increased the crude protein of breast muscle (P<0.05). Each experimental group slightly decreased the drip loss rate of muscle (P>0.05). In addition, GSPE did not show any benefit on pH, incarnadine, moisture or collagen content (P>0.05). In conclusion, as a natural plant dietary substance, GSPE could promote the development of broiler intestinal mucosa and improve the slaughter performance, regulate lipid metabolism, and improve meat quality, particularly with 400 mg/kg GSPE, which provides a new insight into practical application.